Evaluation of green building during occupancy / Fazerra Zainal - Zainal, Fazerra (Faculty of Architecture, Planning and Surveying, 2015)
In the current situation, reducing the consumption of energy from various sectors had been becoming the main agenda for green building development. Green buildings are about resources efficiency, lifecycle effects and building performance while keeping the lowest impact to the environment. However, occupants’ requirements always neglected when indoor environment and quality performance low during occupancy. Therefore, the research was carried out to identify the either relationship between green buildings characteristics can reduce occupants’ satisfaction or not. Then, how the stakeholders overcome these problems can give an example to others for ensuring the status of green buildings.